A strategic approach and business model for scaling up ecosystem-based adaptation for sustainable development in Africa - Munang, Richard; Mgendi, Robert (International Food Policy Research Institute, 2017)
Chapter 10 considers ecosystem-based adaptation and CSA as new paradigms that offer an integrated solution to maximizing the productivity of agriculture and food systems under changing climate regimes. The author posits that ecosystem-based adaptation and CSA offer an opportunity to break from traditional approaches and the silos that have limited the capacity for improving the food security condition of many.